Divergence of Pak-Us Relations during Donald Trump Administration - Dominic, Shahzad; Liaqat, Bilal Bin; Tanveer, Muhammad Usmn (Annals of Human and Social Sciences, 2025)
The objectives of this study is to examine the key political, strategic, and economic factors that contributed to the deterioration of relations between the two nations from 2017 to 2021. The background of the Pak-US relations during the President Donald Trump administration stems from long-standing mistrust, particularly over Pakistan’s role in counterterrorism efforts in Afghanistan. The qualitative data has been collected from academic literature, official government statements, policy documents. The study reveals that Pak-US relations began to fail during the Donald Trump administration due to conflicting strategic interests and growing confusion. Pakistan began to pivot more strongly toward China and other regional allies reducing its reliance on the United States. The overall outcome was a weakened partnership with reduced cooperation in security, economic, and diplomatic spheres. To rebuild trust and cooperation, both Pakistan and the United States should re-establish structured diplomatic dialogues focused on mutual security interests and regional stability